Development of Boccia Cerebral Palsy's National Athlete Achievement in the Indonesian National Paralympic Committee - Mustafa Al Haris; Muchsin Doewes; Hanik Liskustyawati (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
Achievement is the goal for all sports development achievements, the coaching process will affect the results that will be generated. In Indonesia, NPCI is the only organization that facilitates sports with special needs at the international level. Same with normal sports, sports with special needs also have many benefits for each athlete. Boccia is a sport with special needs for children with cerebral palsy in the world. Boccia is a precision sport that anyone can do. Disorders included such as ataxia, hypertonus, atetosis, and limitations in coordination become eligible criteria for boccia sports. The purpose of this research is to find out the fostering of the achievement of the boccia cerebral palsy national altet in the Indonesian National Paralympic Committee. This study uses a qualitative method which was carried out in two places, namely at the NPCI headquarters and the Indonesian national athlete's Boccia Cerebral Palsy Sports Hall in March 2020. Data collection techniques used interviews, observation, and documents. The technique of taking research subjects with purposive sampling with a sample of five people. The results of this study are that the fostering of the achievement of the boccia cerebral palsy national altet in the Indonesian National Paralympic Committee is already in the good enough category but it is still not perfect.